The 2020 Presidential Election and Should Social Media Laws that Affect the Outcome of Intellectual Property Laws Be Dramatically Changed? - L. Buresh, Donald (Journal of Human Psychology, 2022)
In light of the 2020 Presidential election, this essay asks whether social media laws that affect the outcome of intellectual property be dramatically changed. The article outlines the relationship between Section 230 of the Communications Decency Act and the various intellectual property laws, including the four privacy torts, copyright laws, trade secret laws, patent laws, trademark laws, and right of publicity laws. Intellectual property is addressed because intellectual property is typically the content of social media sites. The Communications Decency is analyzed in detail, pointing out that members of both sides of the political aisle seem to believe that the Act gives social media companies tremendous political power to make or break existing members of Congress and future candidates. The paper concludes that the answer to the above question is yes.
Keywords: 2020 Presidential Election; Section 230; Communications Decency Act; Intellectual Property Law; Social Media; Copyright